Use of indocyanine green dye for sentinel lymph node mapping in patients with endometrial cancer and a history of iodinated contrast allergy - Zainab Balogun; Alysia Wiener; Jessica Berger; Jamie Lesnock; Alison A. Garrett (Elsevier, 2024)
Objectives: Sentinel lymph node (SLN) mapping is a surgical technique with high accuracy in detecting metastases while limiting morbidity associated with full lymphadenectomy in endometrial cancer. Cervical injection of indocyanine green (ICG) dye is associated with very high SLN detection rates; however, iodinated contrast allergy has traditionally been viewed as a contraindication to ICG use. The objective of this study was to describe the use of ICG in a population of patients with iodinated contrast allergies undergoing surgical staging for endometrial cancer. Methods: IRB approval was obtained. All patients with clinically early-stage endometrial cancer who underwent minimally invasive surgical staging with SLN mapping with ICG at a single academic institution from 1/1/2017 to 12/31/2020 were identified retrospectively. Patients with reported iodinated contrast allergies prior to surgery were identified. Data were collected through electronic medical record review and compared using descriptive statistics. Results: 820 patients who underwent minimally invasive surgical staging with SLN mapping with ICG were identified, and 25 had documented iodinated contrast allergies. Documented reactions included rash/hives (n = 10, 40 %), anaphylaxis (n = 6, 24 %), shortness of breath (n = 5, 20 %), diarrhea (n = 1, 4 %), and not specified (n = 3, 12 %). A majority (24/25, 96 %) received 4 mg intravenous dexamethasone during induction of general anesthesia as per the institutional enhanced recovery after surgery (ERAS) protocol. No patients experienced allergic reactions or other adverse events after ICG injection. Conclusions: No patients in this cohort demonstrated an adverse reaction after ICG injection for SLN mapping. This study supports the reasonable safety of ICG in patients with contrast allergies, particularly when routine ERAS protocols containing dexamethasone are utilized.